Frequency control scheme for islanded distribution network with high PV penetration / Mohammad Hussein Mohammad Dreidy - Mohammad Hussein, Mohammad Dreidy (2017)
Air pollution due to fossil fuel power plants are causing serious environmental problems, which affect all aspects of life. Due to this, many governments and power utility companies are expressing great interest in Renewable Energy Sources (RESs). Generally, using RESs in a distribution system such as solar Photovoltaic (PV) decreases dependence on fossil fuel. However, at high PV penetration levels, an islanded distribution network suffers from critical frequency stability issues. This occurs due to two main reasons: first, the reduction of the distribution network inertia with high PV penetration, where in this condition, the rate of change of frequency (ROCOF) will be high enough to activate the load shedding controller, even for small power disturbance, and second, this type of networks has a small spinning reserve, where the PV generations are normally providing the maximum output power. The main aim of this research is to develop a comprehensive frequency control scheme for islanding distribution networks with high PV penetration. This scheme is used to stabilize the frequency of the network to a value that is suitable for the islanded and reconnection processes. To achieve this aim, three different controllers were proposed in this scheme; inertia, frequency regulation, and under-frequency load shedding (UFLS) controllers. The inertia controller is designed for PV generation to reduce the network frequency deviation, which is initiated immediately during disturbance event. After a few seconds, a frequency regulation controller, which consists of primary and secondary frequency controllers, is activated. This frequency regulation controller was proposed to provide sufficient power from the Battery Storage System (BSS) to stabilize the frequency within a few minutes. When inertia and frequency regulation controllers fail to stop the frequency deviation, an optimal (UFLS) controller is initiated from Centralized Control System (CCS) to shed the required loads. On top of shedding loads, the CCS is used to manage the operation of frequency control scheme and reconnect the grid. The proposed frequency control scheme and centralized control system were tested using a part of Malaysia’s distribution network (29-bus). The distribution network was modeled and simulated for different PV penetration levels using PSCAD//EMTDC software. The simulation results confirmed that the proposed scheme is able to stabilize the frequency of an islanded distribution network, with 50% PV penetration. This scheme is also capable of recovering the network frequency for small load and radiation changes just before it reaches the load shedding limit (49.5 Hz). Furthermore, at high PV penetration and large disturbance events, the proposed scheme can still recover the frequency by shedding the required loads within (0.254 seconds) without overshooting the frequency. Moreover, when the proposed frequency control scheme is coordinated with CCS, the islanded distribution network will be smoothly reconnected to the main grid. Therefore, this frequency control scheme has potential to be applied in real distribution networks with high PV penetration.